PERAN GURU PENDIDIKAN JASMANIDALAM IKUT MENGEMBANGKAN PERSEPAKBOLAAN NASIONAL - Nurhadi Santoso (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2011)
AbstractPeople used to come to the soccer field to watch a game that is beautifully displayed by the They favouriteplayers and relieve fatigue after working all day. But now, people to the football field are no longer watching thebeautiful game instead of chaos/tumult by players and even by the spectator. Physical education teacher aslearner agents both at school and the community in physical education and sports activities, and thus have amajor contribution to the improvement of football achievements in both school and community. Physical educationteachers are always involved in the learning process of physical activity, where the sport is a vehicle for developmentin physical activity on students taught. physical education teacher who taught some of the vehicle or medium forthe development of physical activity in order to develop physical fitness, motor skills in a variety of physicalactivity, knowledge and positive attitude, honesty, cooperation, perseverance, sportsmanship, and respect forfriends of every physical activity and sport performed. Physical education teachers should provide the knowledge,motor skills, and affective-related rules and techniques of each sport that are taught in their students. Byunderstanding the knowledge, skills, and affective-related rules and techniques of each sport game is good andright (especially soccer) are expected to understand the true learners will game good and not good accordinggame regulations issued by FIFA.AbstractOrang untuk datang ke lapangan sepak bola untuk menonton pertandingan yang indah ditampilkan oleh pemainfavorit mereka dan melepas kepenatan setelah bekerja seharian. Tapi sekarang, orang ke lapangan sepakbolatidak lagi menyaksikan permainan indah, tetapi kekacauan/keributan pemain dan juga penonton. Gurupendidikan jasmani sebagai agen pembelajar, baik di sekolah dan masyarakat dalam pendidikan jasmanidan kegiatan olahraga, dan dengan demikian memiliki kontribusi besar untuk peningkatan prestasi sepakboladi kedua sekolah dan masyarakat. Guru pendidikan jasmani selalu terlibat dalam proses pembelajaran aktivitasjasmani, dimana olahraga adalah kendaraan untuk pembangunan di aktivitas jasmani pada siswa diajarkan,guru pendidikan jasmani yang mengajarkan beberapa media untuk pengembangan aktivitas jasmani dalamrangka untuk mengembangkan kebugaran jasmani, keterampilan motorik dalam berbagai fisik, pengetahuanaktivitas dan sikap positif, kejujuran, kerjasama, ketekunan, sportif, dan menghormati teman-teman dari setiapaktivitas fisik dan olahraga yang dilakukan. Guru pendidikan jasmani harus memberikan pengetahuan,keterampilan motorik, dan afektif yang berhubungan dengan aturan dan teknik dari masing-masing olahragayang diajarkan pada siswa mereka. Dengan memahami pengetahuan, keterampilan, dan afektif yangberhubungan dengan aturan dan teknik setiap permainan olahraga yang baik dan benar (khususnyasepakbola) diharapkan untuk memahami peserta didik yang benar akan permainan yang baik dan tidak baiksesuai peraturan yang dikeluarkan oleh FIFA.Kata kunci: guru, sepakbola, pendidikan jasmani